2015
DOI: 10.1093/jee/tov032
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Formate Fumigation of Dry and Semidry Date Fruits: Experimental Kinetics, Modeling, and Lethal Effect on Carob Moth

Abstract: Ethyl formate (EF) was studied as a fumigant agent with the objective to replace methyl bromide (MB) for date fruit disinfestations. Date fruits Phoenix dactylifera 'Deglet Nour' with different initial moisture content (16% for dry dates, 20% for semidry dates, and a mixture of the two types) were separately fumigated with EF at different concentrations: 28.6, 57.3, 85.9, and 114.6 g/m3 for 2 h. Experimental data of EF sorption during fumigation was successfully fitted to Peleg's model. This model allows the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The phytotoxicity of EF has been previously evaluated for various nursery plants [ 16 ], fruits [ 22 , 23 , 28 ], vegetables [ 34 ] and cut flowers and was suggested to be dependent on the treatment dose, plant species and plant cultivar. For example, when nursery plants were treated with EF, EF phytotoxicity was observed ranging from none (e.g., Ficus benghalensis , Pachira macrocarpa ) to severe (e.g., Anthurium andraeanum , Chamaedorea elegans ) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytotoxicity of EF has been previously evaluated for various nursery plants [ 16 ], fruits [ 22 , 23 , 28 ], vegetables [ 34 ] and cut flowers and was suggested to be dependent on the treatment dose, plant species and plant cultivar. For example, when nursery plants were treated with EF, EF phytotoxicity was observed ranging from none (e.g., Ficus benghalensis , Pachira macrocarpa ) to severe (e.g., Anthurium andraeanum , Chamaedorea elegans ) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, when nursery plants were treated with EF, EF phytotoxicity was observed ranging from none (e.g., Ficus benghalensis, Pachira macrocarpa ) to severe (e.g., Anthurium andraeanum, Chamaedorea elegans ) [ 15 ]. Recently, 4 h EF fumigation was found to be effective at disinfesting invasive pests on a wide variety of products including food commodities, such as banana, citrus, dry dates, and blueberries [ 22 , 23 , 28 , 29 ], and non-food commodities including imported cut flowers and nursery plants [ 16 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 Numerous studies have shown that EF is a potent insecticidal agent and a promising alternative to MB for quarantine and pre-shipment purposes to eliminate several insect pests in food commodities. For example, EF vapour was efficacious in controlling various life stages of spotted wing drosophila (Drosophila suzukii Matsumura), 2,[16][17][18] Planococcus citri Risso (Hemiptera: Pseudococcidae), 15 grain chinch bug (Macchiademus diplopterus), 19 two-spotted spider mites (Tetranychus urticae Koch), 20,21 eucalyptus weevils (Gonipterus platensis Marelli), 22 carob moth (Ectomyelois ceratoniae Zeller), 23 onion thrips (Thrips tabaci), 24 and western flower thrips (Frankliniella occidentalis Pergande). 21 Another potential alternative to MB is chlorine dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, EF has been reported as an effective pesticide for pests in a greenhouse that have developed resistance to other pesticides [ 18 , 19 ]. Several studies have explored the use of EF as a disinfectant on a range of commodities such as fruits, vegetables, nursery plants, and non-food commodities in the condition of post-harvest storage as quarantine purposes, and they have demonstrated its effectiveness [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In this study, we assessed the effectiveness of EF as a disinfectant for A. spiraecola and A. gossypii , two representative aphid species on tropical fruits, on passion fruit.…”
Section: Introductionmentioning
confidence: 99%